Locations of the sacred : essays on religion, literature, and Canadian culture - James, William C. (William Closson), 1943- (Wilfrid Laurier University Press, 1998)
Where do Canadians encounter religious meaning? Not where they used to! In ten lively and wide-ranging essays, William Closson James examines various derivations of the sacred in contemporary Canadian culture. Most of the essays focus on the religious aspects of modern Canadian English fiction -- for example, in essays on the fiction of Hugh MacLennan, Morley Callaghan, Margaret Atwood and Joy Kogawa. But James also explores other, non-literary events and activities in which Canadians have found something transcendant or revelatory. Each of the chapters in Locations of the Sacred can be read independently as a discrete analysis of its subject. Taken as a whole, the essays make up a powerful argument for a new way of looking at the religious in contemporary Canada -- not in the traditional ways of being religious, but in activities and locations previously thought to be "secular." Thus, the domains and modes of the religious are expanded, not restricted